Barbados : 2016 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Barbados. (IMF Staff Country Reports; Country Report, 2016)
This 2016 Article IV Consultation highlights that the economy of Barbados appears to have turned a corner with a pickup in activity. Real GDP grew by 0.8 percent in 2015, underpinned by an increase in private investment and a surge in tourism arrivals, which increased by 14 percent, among the highest in the Caribbean. This boosted employment by 2 percent, while the unemployment rate fell to 11.3 percent. Inflation eased owing to lower import prices, with end-period prices falling by 2.5 percent. Net inflows in the capital and financial account fell, driven by large official amortization payments and lower foreign direct investment. As a result, net international reserves dropped to USD 469 million at the end of April 2016.